COCONUT RESEARCH AND DEVELOPMENT IN THE PHILIPPINES - Dely P. Gapasin (International Coconut Community Journal, 1986)
Research and development programs in agriculture and natural resources are planned, monitored and evaluated by the Philippine government through the Philippine Council for Agriculture and Resources Research and Development (PCARRD) in cooperation with the National Agriculture and Resources Research System (NARRS) and the private sector. Within the NARRS, the Philippine Coconut Authority (PCA) is the national center for coconut research.